Talent transfer: a complementary elite sport development pathway - Cury, R.; Sotiriadou, P.; Kennelly, M. (Managing Sport and Leisure, 2024)
Research question: While talent transition pathways have received substantial research attention in the elite sport development literature, talent transfer initiatives, which enable athletes to transition from one sport to another, have received limited consideration. This research addresses the following question pertaining to elite sport development: What features differentiate structured talent transfer from talent transition pathways? Research methods: This exploratory study draws on expert practitioners` perspectives of talent transfer through semi-structured interviews conducted in 2018 with staff (N = 5) and coaches (N = 5) from an Australian-based program. Results and findings: Differential features of talent transfer identified in this study include accelerated athlete integration into elite sport program, the presence of pre-elite prominent athletic prowess and when compared to talent transition pathways, differentiated skill development progress to the elite level. Additionally, interorganisational collaboration between sports was found to be essential for delivering structured transfer pathways. Implications: The differential features suggest that talent transfer can complement talent transition pathways in elite sport development system. However, talent transfer requires the development of cross-sport collaborations. A structured talent transfer definition is provided in an effort to overcome misconceptions and encourage the integration of talent transfer within elite sport development frameworks and sport policy literature.